(untitled) (Studia theodisca, 2015)
Robert Walser’s robber novel is frequently criticized as an inconsistent and tortuous piece of writing lacking in structure. Moving from these premises, most critics adopt a psychological or psychoanalytic interpretation of this work. My aim is to show that by correlating the main theme of the novel with a motif of Kierkegaard’s Repetition it is possible to better explain what happens in Walser’s text. In this perspective, his novel may be seen as a consequential development of a well-known romantic theme: the mirror theme.